Cloning and characterization of nutrient deficiency and salinity stress responsive TaCBL4 gene from bread wheat (Triticum aestivum L.) - Lekshmy, s; Jha, S K; Chinnusamy, V; Sairam, R K (The Indian Journal of Genetics and Plant Breeding, 2016)
Environmental stresses, such as drought, salinity, extreme temperatures and nutrient deficiencies affect plant productivity adversely. Calcineurin B-like proteins (CBLs) and CBL-interacting protein kinases (CIPKs) are components of calcium mediated stress response pathways in many plants. In the present study, TaCBL4 gene homologous to salt stress responsive Arabidopsis CBL4 (AtSOS3) was cloned from wheat and sequence characterized. The predicted protein of TaCBL4 showed 95, 83, 70 and 61% similarity with amino acid sequences of barley, rice, maize and Arabidopsis CBL4, respectively, demonstrating that CBL4 genes are conserved between dicots and monocots. TaCBL4 protein consists of three EF-hand calcium binding motifs, a characteristic feature of calcium sensor proteins. The modelled image of TaCBL4 protein was highly identical to the already resolved structure of the AtCBL4 protein. In addition to salinity stress, the expression of TaCBL4 gene was also up-regulated by deficiency of major nutrients, namely, nitrogen, phosphorus and potassium. This suggests that TaCBL4 may serve as node for signaling crosstalk between salinity and nutrient deficiency stress signaling pathways and nutrient homeostasis under salinity stress. The present study lays foundation for functional studies on role of TaCBL4 gene in nutrient use efficiency and for its further utilization in breeding new wheat varieties with enhanced nutrient use efficiency and salinity tolerance.